2001
DOI: 10.1002/ar.1104
|View full text |Cite
|
Sign up to set email alerts
|

Luminal morphology of the avian lower intestine: Evidence supporting the importance of retrograde peristalsis for water conservation

Abstract: Tissue from the lower intestine of two species of sparrow, the house sparrow Passer domesticus and savannah sparrow Passerculus sandwichensis was sectioned in an unbiased manner and examined quantitatively using stereology. The tissue was processed for light microscopy, and scanning and transmission electron microscopy to examine the extent to which microvilli enhanced the epithelial surface area of the cecae, rectum, and coprodeum. Parameters measured included individual microvillus surface area, microvilli p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
(33 reference statements)
2
9
1
Order By: Relevance
“…In birds, water moves retrogradely towards the cecae from the coprodeum, whose squamous epithelium is not conducive to water reabsorption. This orad movement allows ureteral urine to pass over the villi of the rectum whose epithelium has a high surface area and packing density that is conducive to water reabsorption (Casotti, 2001a). Coinciding with this, the present study found AQP-1 in the epithelium of the distal rectum.…”
Section: Discussionsupporting
confidence: 80%
“…In birds, water moves retrogradely towards the cecae from the coprodeum, whose squamous epithelium is not conducive to water reabsorption. This orad movement allows ureteral urine to pass over the villi of the rectum whose epithelium has a high surface area and packing density that is conducive to water reabsorption (Casotti, 2001a). Coinciding with this, the present study found AQP-1 in the epithelium of the distal rectum.…”
Section: Discussionsupporting
confidence: 80%
“…The results of present study showed that the villi and mucosal surface area and villi amplification factor decreased with distance distally (from S1 towards S3) along the intestinal tract of both species chickens. Although there was no significant difference among the desired parameters between both species, disproportionate alterations were separately observed between segments 1 and 3 at each species, which is in agreement with the results obtained about those of sparrow on the lower intestine (Casotti 2001). Also, in the present study, it was shown that in both species, the microvilli absolute surface area and packing density of the R-C segment in chickens decreased from proximal towards distal.…”
Section: Discussionsupporting
confidence: 92%
“…Birds do not have an actual urinary bladder; therefore after urine is formed by the kidneys, it moves in the ureters' tract and finally all will be entered into the cloaca (a blind pouch). Urine may travel in a reverse direction and enter into the lower intestine by retrograde peristalsis (Duke 1989;Clauss et al 1991;Brummermann and Braun 1994;Casotti 2001). Retrograde peristalsis in lower intestine causes urine to reach the regions of microbial fermentation in ceca or upper colon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most birds studied so far present retrograde flow transport of fluid from the urodeum to the coprodeum and, with few exceptions, to the colon and even the caeca (Akester et al, 1967;Skadhauge, 1977;Skadhauge et al, 1984;Braun, 1999;Goldstein and Skadhauge, 2000;Casotti, 2001). Reptiles share similar strategies for postrenal osmoregulation (Junqueira et al, 1966;Skadhauge, 1977;Bradshaw and Rice, 1981;Taplin and Loveridge, 1988;Pidcock et al, 1996;Goldstein and Skadhauge, 2000;Kuchel and Franklin, 2000).…”
Section: ; Vanmentioning
confidence: 99%